2005
DOI: 10.1161/circulationaha.105.546812
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-Mediated Endothelial Nitric Oxide Synthase Association With Heat Shock Protein 90 Requires Adenosine Monophosphate-Dependent Protein Kinase

Abstract: Background-Estradiol activates endothelial nitric oxide synthase (eNOS) by mechanisms that involve estrogen receptor-␣ (ER␣), protein kinase B/Akt, mitogen-activated protein kinases, and heat shock protein 90 (HSP90). Recently, AMP-activated protein kinase (AMPK), an enzyme that plays a crucial role in cellular adaptation to metabolic stress, has been implicated in physiological eNOS activation by the hormones adiponectin and insulin. We therefore investigated whether AMPK is activated by estradiol in endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 46 publications
7
90
2
Order By: Relevance
“…However, the increase of the AMPK activation state induced by 17-estradiol treatment seems to be sufficient to phosphorylate HMGR and to restore its proper activity. The enhancement of estradiol-induced AMPK activation is supported also by other data in the literature (Schulz et al, 2005). …”
Section: Discussionsupporting
confidence: 84%
“…However, the increase of the AMPK activation state induced by 17-estradiol treatment seems to be sufficient to phosphorylate HMGR and to restore its proper activity. The enhancement of estradiol-induced AMPK activation is supported also by other data in the literature (Schulz et al, 2005). …”
Section: Discussionsupporting
confidence: 84%
“…As AMPK is quite sensitive to changes in the AMP/ATP ratio, this effectively reduces AMPK activation. 39 In our studies, we found that pre-treatment with either Ara-A or 59-iodotubercidin inhibited AMPK phosphorylation as determined by western blot analysis following EGCG treatment (Figure 6a). Although both inhibitors prevented AMPK phosphorylation, iNOS protein expression, supernatant NO levels and IL-6 production were still inhibited following EGCG treatment (Figure 6b-d).…”
Section: Egcg Inhibits Inflammation In Lupus Mesangial Cellsmentioning
confidence: 55%
“…This temporal response is similar to that stimulated by shear stress, by adiponectin and by metformin. [25][26][27][28] Sun et al 13 showed that the phosphorylation/ activation of AMPK in mouse aorta and myocardium was observed as early as 2 h and peaked at 4-8 h after atrovastatin administration. However, the role of AMPK in angiogenesis in vivo has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%